PENDIDIKAN KARAKTER MELALUI METODE KEPRAMUKAAN DI SEKOLAH DASAR TAMAN MUDA JETIS YOGYAKARTA - Dwi Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2017)
This research aims to : (1) Know and describe in applying the education character hrough the Scouting Method at SD Taman MudaJetis Yogyakarta, (2) describe the learning process of scouting method to build student’s character at SD Taman MudaJetis Yogyakarta (3) identify obstacle in applying the education chacater through the scouting method at SD Taman MudaJetis Yogyakarta, and find solutions to overcome the obstacles.This was a qualitative research. In order to gain data, the researcher used direct observation, indept interview, and documentation. The data analysis techniques are data reduction, data categorize, data display and verification, while the data validation included internal validation, external validation, reliability and objectivity.The result of the research showed that: (1) The Learning to use scouting methods in SD Taman Muda Jetis Yogyakarta done through a variety of methods with in the context of scouting methods. The methods used include other outbond, ceremony, game, scouting skills, scouting challenge, a media based approach to Information Technology. (2) The planting pf character values such as discipline was done with the ceremony, and exercise. Asense of responbility and competition honed through scouting skills, scouting challenge. In adition so that learners have the knowledge and not but of date then use a media based approach to Information Technology. The learning prsocess with methods of scouting can be done as following : (a) Experience, (b) Reflect, (c) Form Concept, (d) Test Concept. (3) The planting of character values of scouting had a few obastacles, among other: Limited land the school, Lack of facilities and infrastructure in the implementation of activities. lack of teachers who stand as a builder because it should have a base there must be a scoutmaster sons and daughters in every level, as well as the limitations of time and cost to implement the methods Visit. The steps taken to overcome the obstacles, among others, include alumni high school desk in first and senior high schoolto also train the scouts in primary school, propose to the school to hold the branch quarter in order to participate in providing materials refresher training with Regency Council and Distric Council every 3 months, as well as their regular meetings between the principals, teachers and staff are held every 3 months for monitoring and evaluation of the learning process that takes place both intra and extra.